Detection of mycoplasma hyopneumoniae and porcine reproductive and respiratory syndrome in clinical samples by polymerase chain reaction - Liew, Yew Seng; Ooi, Peck Toung (2011)
The aim of this study was detect Swine Enzootic Pneumonia (SEP) and Porcine Reproductive and Respiratory Syndrome (PRRS) from clinical affected lung samples with PCR technique. In this technique three primers set used for M. hyopneumonieae detection were Cai (Forward: GAG CCT TCA AGC TIC ACC AAG A: Reverse: TGT GTT AGT GAC TTT TGC CAC C), Baumeister (Forward: TAG AAA TGA CTG GCA GAC AA: Reverse: GAG GCT TGA TTT TGG AGT C) and Caron (Forward: GAC CCG ATG AAA CCT ATT AAA ATA GAC: Reverse; GAA GCG AAA TTA AAT ATT TTT AAT TCG ATA CTG). For the detection of PRRS virus the primer sets used Oleksievicz (Forward: GAA CCT GCC CAI CAC G: Reverse: TAC CCC TAA TTG AAT AGG GGA) amd Suàrez )Forward: GGG AAT GGC CAG CCA GTC AAT CAA CTG T: Reverse: TGT AGA AGT CAC GCG AAT CAG GCG CAC T). Nine pigs aged betwee 6-10 weeks were collected from farms in Selangor, Malaysia. One healthy pig and 8 other pigs with clinical signs of respiratory distress problem were sacrificed and lung bronchoalveolar lavage samples were obtained. Healthy pigs were selected as negative control while samples were harvested from 4 pigs with suspected SEP and 4 with respiratory problems for M. hyoneumoniae and PRRS virus detection. Base on the result, the Caronand Caiprimer sets were able to detect SEP from the affected lungs. For PRRS virus, RNA was extracted using easy-BLUE™ Total RNA Extraction Kit and converted it to cDNA with Maxime RT PreMix Kit. The oleksiewicz primer set was ideally suited for the detection of PRRS virus.